Strategi Distribusi PT. Mitra Adiperkasa TBK (MAP) - Erli Azzahra Putri; Rayhan Rugasa; Nofriandi Putra; Ahmad Fajri Rahman (CV. ITTC INDONESIA, 2026)
This study analyzes the distribution strategy of PT Mitra Adiperkasa Tbk (MAP) as one of Indonesia's largest retail companies. Distribution plays a crucial role in marketing success, especially in modern retail that faces challenges from changing consumer behavior and digital transformation. This research employs a qualitative descriptive approach through secondary data analysis from company reports, academic literature, and relevant publications. The findings indicate that MAP implements an integrated distribution system by combining roles as license holder, importer, distributor, and retailer. MAP's distribution strategy is characterized by an omni-channel approach integrating physical stores and digital platforms, supported by robust logistics infrastructure and data-driven inventory management. The multilevel distribution channel structure provides operational flexibility while maintaining service quality control. The study concludes that distribution serves as a strategic foundation for MAP's competitiveness in the Indonesian lifestyle retail industry. This research contributes to understanding how distribution strategies can create competitive advantage and enhance customer experience in the modern retail context.